Muslims Celebrate Ramadan (African Knowledges and the History Publication since the 1970s)
Muslim men and children hold Ramadan prayer in Antoinette Tubman Stadium in Monrovia.
Keywords: Islam; Religion; Prayer; Ramadan; Celebration